Establishing the characteristics for patients with chronic Complex Regional Pain Syndrome: the value of the CRPS-UK Registry. Issue 2 (May 2015) - Shenker, Nicholas; Goebel, Andreas; Rockett, Mark; Batchelor, James; Jones, Gareth T; Parker, Richard; de C Williams, Amanda C; McCabe, Candida
Objective: The long-term prognosis of patients with Complex Regional Pain Syndrome (CRPS) is unknown with no reported prospective studies from the United Kingdom longer than 18 months. The CRPS-UK Network aims to study this by use of a Registry. The aims of this article are, to outline the CRPS-UK Registry, assess the validity of the data and to describe the characteristics of a sample of the UK CRPS population. Methods: A web-based CRPS-UK Registry was developed and made accessible to centres experienced in diagnosing and managing patients with CRPS. Pragmatic annual follow-up questions were agreed. Results: Up until July 2013, the Registry has recruited 240 patients. A blinded, validation study of 20 consecutive patients from two centres (10 each) demonstrated 95.6% completion and 99.4% accuracy of a random sample of the recorded data. These patients had chronic disease (median duration: 29 months); 72.5% were female (2.6:1), with a mean age at symptoms onset of 43 years, and were left-handed more than expected (21.8% versus 10% in the general population). Patients reported a delayed diagnosis, with the median time between symptom onset and diagnosis of 6 months. In all, 30 patients (12.5%) had multiple limb involvement and (83.3%) had a contiguous spread of CRPS. Conclusion: CRPS-UK Registry is a validated method for actively recruiting well-characterised patients with CRPS to provide further information on the long-term outcome.